Impact of Local and Systemic Factors on Kidney Dysfunction in Bardet-Biedl Syndrome - Miriam Zacchia; Giovanna Capolongo; Francesco Trepiccione; Vincent Marion (Karger Publishers, 2017)
Bardet Biedl syndrome (BBS) is a rare inherited syndromic condition characterized by renal and extra-renal disorders. Renal defect, at either structural or functional level, is one of the cardinal clinical features, and is a major cause of morbidity. However, the pathogenic mechanism underlying its dysfunction remains largely unknown, and to date only symptomatic treatment with no specific therapy is available for these patients. Elucidating aberrant cellular and/or systemic processes that impact kidney function is therefore a prerequisite to develop targeted innovative therapeutic strategies for the BBS patients. Given the proven role of BBS proteins in the function of the primary cilium (PC) and considering the clinical overlapping of BBS with other ciliopathies, BBS is considered the result of disruption of ciliary activities. The present review aims at giving an updated overview of the spectrum of renal abnormalities in BBS patients according to the existing scientific literature, and discusses the possible role of intrinsic PC dysfunction into the pathogenesis of renal defects based on the most recent findings demonstrating a possible role of systemic factors in favoring the progression of renal disease.